Orai1 Expression and Vascular Function in Kidney Donors Determine Graft Outcomes at Short/Mid-Term - Esther García-Rojo; Javier Angulo; Mariam El Assar; Rocío Santos-Pérez de la Blanca; Borja García-Gómez; José Medina-Polo; Alejandro Sevilleja-Ortiz; Leocadio Rodríguez-Mañas; Argentina Fernández; Eduardo Gutiérrez-Martínez; Enrique Morales-Ruiz; Alfredo Rodríguez-Antolín; et al. (Cells)
We aimed to determine the influence of donors’ vascular function on renal function in recipients and to evaluate the role of Orai1 calcium channels as a potential marker. A prospective collaborative multicenter study was designed. Blood, aorta (HA), mesenteric arteries (HMAs) and corpus cavernosum (HCC) specimens were obtained from organ donors at the kidney procurement procedure (n = 60). Evolution (up to 2 years) of renal function measured as serum creatinine (SCr) and glomerular filtration rate (GFR) was evaluated in respective recipients (n = 64). Vascular responses were determined in HA, HMA and HCC from donors. Tumor necrosis factor-α, asymmetric dimethyl arginine and Orai1 were measured in plasma. Orai1 protein expression was also evaluated in each donor’s aorta. Endothelium-dependent vasodilation (HMA, HCC) and adrenergic contraction (HA) in donors determined renal function in recipients, 12 months post-transplantation. Donors in the best quartile of vascular function predicted lower SCr and higher GFR in kidney recipients for 12/24 months. Plasma Orai1 in donors was negatively correlated with vascular function and predicted renal function at 3–6 months post-transplantation. Donor Orai1 vascular content was associated with reduced vascular function and with poorer recipient renal function for 1-year post-transplantation. Systemic vascular function of kidney donors determines recipients’ renal function at short/mid-term. Donors’ vascular function and recipients’ renal function are negatively associated with donors’ Orai1 vascular expression, being a potential biomarker of renal outcomes.